2019
DOI: 10.2147/cmar.s217944
|View full text |Cite
|
Sign up to set email alerts
|

<p>Low-Concentration PTX And RSL3 Inhibits Tumor Cell Growth Synergistically By Inducing Ferroptosis In Mutant p53 Hypopharyngeal Squamous Carcinoma</p>

Abstract: Introduction: RSL3-induced ferroptosis is a cell death pathway dependent upon intracellular iron and is characterized by accumulation of lipid hydroperoxides. Glutaminolysis, a glutamine-fueled intracellular metabolic pathway, is an essential pathway of ferroptosis in cancer cells. Recent findings showed low-concentration paclitaxel (PTX) could inhibit cell death by upregulating p53 expression; downregulating glutaminolysis-related genes. Methods: The therapeutic effect of RSL3 plus low-concentration PTX combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 36 publications
0
42
0
Order By: Relevance
“…Ye and his colleagues demonstrated that the combination of PTX and RSL3 rather than each agent alone induced ferroptosis in hypopharyngeal squamous carcinoma (HPSCC) cells with mutant p53 (mtp53) through the suppression of SLC7A11. mtp53 expression and, especially, the acetylation of K98 play a key role in PTX and RSL3-induced ferroptosis (33). In addition, a low dose of erastin can dramatically promote the therapeutic effects of cytarabine/ara-C and doxorubicin/adriamycin against leukemic cells in an RAS-independent manner that depends partly on ferroptosis induction.…”
Section: The Role Of Ferroptosis In Mainstream Cancer Treatments Ferrmentioning
confidence: 99%
“…Ye and his colleagues demonstrated that the combination of PTX and RSL3 rather than each agent alone induced ferroptosis in hypopharyngeal squamous carcinoma (HPSCC) cells with mutant p53 (mtp53) through the suppression of SLC7A11. mtp53 expression and, especially, the acetylation of K98 play a key role in PTX and RSL3-induced ferroptosis (33). In addition, a low dose of erastin can dramatically promote the therapeutic effects of cytarabine/ara-C and doxorubicin/adriamycin against leukemic cells in an RAS-independent manner that depends partly on ferroptosis induction.…”
Section: The Role Of Ferroptosis In Mainstream Cancer Treatments Ferrmentioning
confidence: 99%
“…SLC7A11 is a major component of System X C − and the latter is indispensable for importing cystine, which is used to synthesize antioxidant GSH [19,44]. Previous studies have demonstrated that p53 directs the transcriptionally suppressed SLC7A11 expression [41,45,46], thereby suppressing system X C − activity to trigger ferroptosis. In a similar mechanism depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5c). Ye et al 241 investigated the effect of the combined administration of paclitaxel and RSL3: alone and at low concentrations, these agents do not cause substantial cell death. Low-concentration paclitaxel (3-6 nM) is reported to interfere with glutaminolysis, a process that is essential for ferroptosis.…”
Section: Drug Combinationsmentioning
confidence: 99%